PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN AIR HUJAN SEBAGAI SUMBER AIR BERSIH “URBAN FARMING” DI WILAYAH CIBABAT CIMAHI (Poltekkes Kemenkes Bandung, 2023)
Another use of rainwater is as raw water for clean water and drinking water, but of course, this use must have the support of the community as a beneficiary resource. The results of the study show that rainwater in urban areas is influenced by local pollutant sources as well as long-distance transport of natural and anthropogenic air pollutants. The concept of urban farming is one of the solutions by creating green open land amidst the density of buildings in the urban area of Cimahi; so that the environment is expected to be comfortable and healthy. The hydroponic method is an agricultural system that is carried out using water-growing media without using soil, so it is more efficiently applied to areas with sufficient water availability. Therefore this needs to be supported by the availability of clean water as a planting medium by utilizing rainwater. This community service activity will try to utilize rainwater that has been treated using a rainwater processing installation; so that the harvest produced does not have a risk of impact on health if consumed. Counseling and training activities on processing rainwater into clean water for